CircRNA_100395 Carried by Exosomes From Adipose-Derived Mesenchymal Stem Cells Inhibits the Malignant Transformation of Non-Small Cell Lung Carcinoma Through the miR-141-3p-LATS2 Axis - Zhang, Chong; Cao, Jinlin; Lv, Wang; Mou, Haibo (Frontiers in Cell and Developmental Biology, 2021)
Objective: The specific purpose of this study is to investigate the impact exosomes from adipose-derived mesenchymal stem cells (AMSCs) has on non-small cell lung carcinoma (NSCLC) and the relative applications. Methods: circRNA_100395, miR-141-3p and LATS2 were expressed and detected in NSCLC and paracancerous tissues as well as NSCLC cell lines. Pearson correlation analysis, Dual-Luciferase Reporter Assay and RNA pull-down assay were used to validate their expression and interaction respectively. After isolation and culture of AMSCs, exosomes were extracted and identified. EdU, Epithelial-Mesenchymal Transition (EMT) and cell colony formation assay were used to distinguish the biological activity of the cells. Expression Hippo/YAP signalling pathway-related proteins were measured by western blotting. Subsequently, tumour volume and weight were confirmed based on xenograft nude mice models, Ki-67 and LATS2 expression was observed by immunohistochemistry. Results: circRNA_100395 was lowly expressed in NSCLC tissues or cells. The negative correlations and interactions were confirmed between circRNA_100395 and miR-141-3p, miR-141-3p and LATS2. AMSC-derived exosomes with overexpression of circRNA_100395 (exo- circRNA_100395) significantly inhibited the biological activity as well as EMT of H1650 cells and Hippo/YAP signalling pathway activity. In addition, exo-circRNA_100395 markedly reduced tumour volume and weight as well as Ki-67 and LASP1 expression in vivo. However, overexpressed miR-141-3p or knocked down LATS2 alleviated the above effects. Conclusion: Exo-circRNA_100395 can increase LATS2 expression by sponging miR-141-3p to regulate Hippo/YAP signalling pathway, thereby inhibiting NSCLC malignant transformation.